Development of a novel general reconfigurable vehicle dynamics model. (February 2021) - Ataei, Mansour; Khajepour, Amir; Jeon, Soo
Highlights: A unified reconfigurable vehicle dynamics model is developed in this study. A novel approach in vehicle modeling is presented to develop the proposed model. The model can be configured for different four- and three-wheeled vehicles. Wheels and actuators can readily be added or removed using the defined matrices. Included actuators are active steering, differential braking and torque vectoring. Abstract: This study presents a novel approach in vehicle modeling to provide a unified reconfigurable vehicle dynamics model. The introduced vehicle model is applicable for analysis, design, and control of a wide variety of vehicles and can be reconfigured for four- and three-wheeled vehicles. Active steering, differential braking, torque vectoring, and active camber are included in the model as the actuators. The proposed set of model equations is reconfigurable and can be adjusted for various vehicles without need for new derivation. Two matrices are defined called the corner reconfiguration matrix and actuator reconfiguration matrix that are responsible for wheel and actuator configurations of the vehicle, respectively. The model can be reconfigured by setting the diagonal elements of these two matrices. The proposed reconfigurable model is compared with different high-fidelity vehicle models in CarSim for validation. Simulation results show that four-wheeled and three-wheeled vehicle models can all be drawn from the single unified reconfigurable model. In addition, the introduced model properly matches the high-fidelity CarSim models for four-wheeled and three-wheeled vehicles.